Towards a better understanding of deep-sea tardigrade biogeography: numerous new records from the Southern Ocean - Trokhymchuk, Roman; Schmidt-Rhaesa, Andreas; Utevsky, Serge; Kristensen, Reinhardt Møbjerg; Kieneke, Alexander (Zootaxa, 2024)
To date, only eight species of marine tardigrades have been recorded from the Southern Ocean. A total of 1210 tardigrade specimens were collected during various marine expeditions with R/V POLARSTERN: ANDEEP-1, ANDEEP-2, ANDEEP-3 and ANDEEP-SYSTCO. The sampled tardigrades belong to five families (Batillipedidae, Coronarctidae, Halechiniscidae, Styraconyxidae and Echiniscoididae), seven genera (Batillipes, Coronarctus, Moebjergarctus, Angursa, Styraconyx, Tholoarctus, Isoechiniscoides) and 15 species (Batillipes wyedeleinorum, Coronarctus dissimilis, Coronarctus tenellus, Coronarctus cf. tenellus, Moebjergarctus clarionclippertonensis, Angursa sp., A. abyssalis, A. antarctica, A. capsula, A. lanceolata, A. lingua, Styraconyx qivitoq, S. takeshii, Tholoarctus oleseni, Isoechiniscoides aff. sifae sp. can.). For the genera Batillipes, Coronarctus, Moebjergarctus, Tholoarctus and Isoechiniscoides, these new distribution data are the southernmost records and first reports from the Southern Ocean. Furthermore, the genera Styraconyx, Batillipes and Isoechiniscoides are reported from the abyssal zone for the first time. These new findings significantly expand our previous knowledge of both geographic and bathymetric distribution of marine Tardigrada.